Motivational factors and differences between part-time & full-time employees of Grameenphone Ltd. -contact center - Abonty, Sabera Zohra (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.